2023
DOI: 10.2147/ijn.s399487
|View full text |Cite
|
Sign up to set email alerts
|

Sericin/Nano-Hydroxyapatite Hydrogels Based on Graphene Oxide for Effective Bone Regeneration via Immunomodulation and Osteoinduction

Abstract: Background Immune responses and osteogenesis differentiation induced by implants are crucial for bone tissue regeneration. Consideration of only one of those properties is not sufficient. To investigate the synergistic actions, we designed alginate/graphene oxide/sericin/nanohydroxyapatite (Alg/GO/Ser/nHAP) nanocomposite hydrogels with both osteoimmunomodulatory and osteoinductive activities. This study aimed to explore the effect of hydrogel with osteoimmunomodulatory properties on promoting oste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…It has been demonstrated that GO-based nanocomposites can promote the polarization of M1 to M2 macrophages for regulating the immune microenvironment [ 72 ]. For instance, Fu et al developed a GO-based composite hydrogel (Alg/GO/Ser/nHAP) that fostered conducive bone growth and bone immune microenvironment, which enhanced the osseointegration process at the bone–implant interface by shifting the macrophage phenotype from M1 to M2 [ 41 ]. Similarly, Xue et al found that quaternized chitosan scaffolds with GO modification were more effective than pure quaternized chitosan scaffolds in promoting the polarization of M2-type macrophages and osteogenesis [ 73 ].…”
Section: The Advantages Of Using Go-based Nanomaterials In the Treatm...mentioning
confidence: 99%
“…It has been demonstrated that GO-based nanocomposites can promote the polarization of M1 to M2 macrophages for regulating the immune microenvironment [ 72 ]. For instance, Fu et al developed a GO-based composite hydrogel (Alg/GO/Ser/nHAP) that fostered conducive bone growth and bone immune microenvironment, which enhanced the osseointegration process at the bone–implant interface by shifting the macrophage phenotype from M1 to M2 [ 41 ]. Similarly, Xue et al found that quaternized chitosan scaffolds with GO modification were more effective than pure quaternized chitosan scaffolds in promoting the polarization of M2-type macrophages and osteogenesis [ 73 ].…”
Section: The Advantages Of Using Go-based Nanomaterials In the Treatm...mentioning
confidence: 99%
“…Implanted in rat calvarial defects, the scaffold facilitated new bone regeneration within 12 weeks by inducing autologous bone marrow-derived mesenchymal stem cell differentiation [ 57 ]. Further research by Fu et al [ 58 ] explored the combination of sericin with nanohydroxyapatite and graphene oxide in an alginate-based nanocomposite hydrogel. This scaffold not only promotes osteogenesis but also creates a favorable osteoimmune microenvironment by inducing M2 macrophage polarization [ 58 ].…”
Section: Comparative Analysismentioning
confidence: 99%
“…Further research by Fu et al [ 58 ] explored the combination of sericin with nanohydroxyapatite and graphene oxide in an alginate-based nanocomposite hydrogel. This scaffold not only promotes osteogenesis but also creates a favorable osteoimmune microenvironment by inducing M2 macrophage polarization [ 58 ]. The synergistic effect of immunomodulation and osteoinduction exhibited by this scaffold leads to effective bone regeneration [ 58 ].…”
Section: Comparative Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…macrophages) before the arrival of mesenchymal stem cells (MSCs). In recent years, the development of osteoimmunology has revealed that the degree of inflammation significantly affects the performance of orthopedic implants [3]. Excessive and chronic inflammation may cause the formation of fibrous capsules, resulting in implant failure, while, mild inflammation may induce new bone formation and enhance implant integration [4].…”
Section: Introductionmentioning
confidence: 99%